FLT3-ITD Allelic Burden and Acute Promyelocytic Leukemia Risk Stratification - Li, Andrew Y. (Biology (Basel), 2021)
SIMPLE SUMMARY: Around 12–38% of acute promyelocytic leukemia (APL) patients carry the FLT3-ITD mutation, which has been associated with several poor-prognosis indicators such as high white blood cell counts, M3v variant morphology, and the bcr3 isoform. We aimed to retrospectively study the impact of FLT3-ITD mutations in APL patients in regard to clinical features, treatment courses, and outcomes. We demonstrate that Sanz high-risk status APL correlates with high FLT3-ITD allelic burdens, with every 1% increase in allelic burden correlating with a 0.6 × 10(9)/L increase in white blood cell count (WBC). The presence of FLT3-ITD was associated with decreased remission rates and higher 5-year mortality from the time of diagnosis. These findings provide novel revelations regarding the features of FLT3-ITD APL, particularly in regard to allelic burden, that warrant further study. ABSTRACT: The significance of FLT3-ITD in acute promyelocytic leukemia (APL) is not well-established. We performed a bi-center retrospective study of 138 APL patients, 59 (42.8%) of whom had FLT3-ITD. APL patients with FLT3-ITD had higher baseline white blood cell counts (WBCs) (p < 0.001), higher hemoglobin, (p = 0.03), higher aspartate aminotransferase (p = 0.001), lower platelets (p = 0.004), lower fibrinogen (p = 0.003), and higher incidences of disseminated intravascular coagulation (p = 0.005), M3v variant morphology (p < 0.001), and the bcr3 isoform (p < 0.001). FLT3-ITD was associated with inferior post-consolidation complete remission (CR) (p = 0.02) and 5-year overall survival (OS) of 79.7%, compared to 94.4% for FLT3-WT (wild-type) (p = 0.02). FLT3-ITD was strongly associated with baseline WBCs ≥ 25 × 10(9)/L (odds ratio (OR): 54.4; 95% CI: 10.4–286.1; p < 0.001). High FLT3-ITD allelic burdens correlated with high-risk (HR) Sanz scores and high WBCs, with every 1% increase in allelic burden corresponding to a 0.6 × 10(9)/L increase in WBC. HR APL was associated with a 38.5% increase in allelic burden compared with low-risk (LR) APL (95% CI: 19.8–57.2; p < 0.001). Our results provide additional evidence that FLT3-ITD APL is a distinct subtype of APL that warrants further study to delineate potential differences in therapeutic approach.